Simulating vortex induced vibration of an impulsively started flexible filament by an implicit IB–LB coupling scheme. (1st January 2020) - Wu, Jiayang; Cheng, Yongguang; Zhang, Chunze; Diao, Wei
Abstract: All explicit immersed boundary–lattice Boltzmann (IB–LB) coupling schemes suffer from instability and restrictive choices of timestep and boundary rigidity. In this paper, an implicit IB–LB coupling method that can greatly alleviate those problems and easily incorporate the boundary mass is presented. The nonlinear equations resulting from the implicit discretization of the immersed boundary (IB) equations are solved by the Jacobian-free Newton–Krylov (JFNK) method, while the boundary mass is handled by introducing ghost boundaries. The improvement in stability is verified by two benchmark cases, and it is evident that both the maximal timestep and bending rigidity attained by the proposed implicit method can increase up to 200 times compared with those of the explicit version. The new method is applied to analyzing the vortex induced vibration of an impulsively started flexible filament, and both the simulated flow field and filament motion agree well with those obtained by particle image velocimetry (PIV). The influences of filament parameters on the vibration characteristics are discussed, and according to the results, the filament mass is the main influencing factor of vibration amplitude and the bending rigidity is the main influencing factor of vibration frequency.